Comprehension of an electronic document- what readers do and do not do - Protopsaltis, Aristidis; Bouki, Vasiliki (The Sixteenth Triennial Conference of the International Federation of Operational Research Societies, 2002)
This study aims to investigate the cognitive aspects of discourse processing in an electronic environment with the use of think-aloud protocols. This study is a pilot study and it is part of a more extensive research. A cognitive model has been proposed to account for reading comprehension in an electronic environment. An experiment has been designed to assess this model. The objectives of the experiment are to study the cognitive processes and the reading strategies that are necessary during the reading of information on the WWW. Eight subjects have taken part in this pilot phase of the experiment. The subjects read the document for as long as they felt confident that could answer questions about it. All subjects answer the same set of question